Recording type 2 diabetes mellitus in a standardised central Saudi database: a retrospective validation study - Althunian, Turki Abdulaziz; Alrasheed, Meshael M; Alnofal, Fatemah A; Tafish, Rawan T; Mira, Mahmood A; Alroba, Raseel A; Kirdas, Mohammed W; Alshammari, Thamir M (BMJ open, 2023)
ObjectivesThis study was conducted to assess the validity of recording (and the original diagnostic practice) of type 2 diabetes mellitus at a hospital whose records were integrated to a centralised database (the standardised common data model (CDM) of the Saudi National Pharmacoepidemiologic Database (NPED)).DesignA retrospective single-centre validation study.SettingsData of the study participants were extracted from the CDM of the NPED (only records of one tertiary care hospital were integrated at the time of the study) between 1 January 2013 and 1 July 2018.ParticipantsA random sample of patients with type 2 diabetes mellitus (≥18 years old and with a code of type 2 diabetes mellitus) matched with a control group (patients without diabetes) based on age and sex.Outcome measuresThe standardised coding of type 2 diabetes in the CDM was validated by comparing the presence of diabetes in the CDM versus the original electronic records at the hospital, the recording in paper-based medical records, and the physician re-assessment of diabetes in the included cases and controls, respectively. Sensitivity, specificity, positive predictive value and negative predictive value were estimated for each pairwise comparison using RStudio V.1.4.1103.ResultsA total of 437 random sample of patients with type 2 diabetes mellitus was identified and matched with 437 controls. Only 190 of 437 (43.0%) had paper-based medical records. All estimates were above 90% except for sensitivity and specificity of CDM versus paper-based records (54%; 95% CI 47% to 61% and 68%; 95% CI 62% to 73%, respectively).ConclusionsThis study provided an assessment to the extent of which only type 2 diabetes mellitus code can be used to identify patients with this disease at a Saudi centralised database. A future multi-centre study would help adding more emphasis to the study findings.